2022
DOI: 10.1055/s-0042-1757753
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Headache Disorders: Approach, Workup, and Special Considerations for Select Populations

Abstract: Headache is one of the most common diagnoses in neurology. A thorough understanding of the clinical presentation of secondary headache, which can be life-threatening, is critical. This review provides an overview of the diagnostic approach to a patient with headache, including discussion of “red,” “orange,” and “green” flags. We emphasize particular scenarios to help tailor the clinical workup to individual circumstances such as in pregnant women, when particular attention must be paid to the effects of blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The density of headaches (the number of days with headache per month) was different between the regions (p < 0.001). In pairwise comparisons, it was detected that the patients in Africa (5.93 ± 1.06 [0–30]) referred to the hospital with a lower density of headaches than those in Turkey (11.68 ± 0.53 [0–30]), the Middle East (15.97 ± 1.73 [230]), and Asia (11.19 ± 2.15 [0–30]) (p < 0.001) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The density of headaches (the number of days with headache per month) was different between the regions (p < 0.001). In pairwise comparisons, it was detected that the patients in Africa (5.93 ± 1.06 [0–30]) referred to the hospital with a lower density of headaches than those in Turkey (11.68 ± 0.53 [0–30]), the Middle East (15.97 ± 1.73 [230]), and Asia (11.19 ± 2.15 [0–30]) (p < 0.001) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The severity and density of headaches play a crucial role in diagnosing and treating secondary headache disorders (17). A recent systematic review emphasized their significance and suggested thorough evaluations for patients with severe or persistent headaches (18). Our study observed significant differences in pain severity and density among regions, with patients from Africa reporting milder pain.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that some COVID-19 cases can be associated with cerebrovascular complications. Patients with these symptoms should be urgently sent for the appropriate neuro-imaging studies [15 ▪ ].…”
Section: Headache As a Symptom Of Acute Coronavirus Disease 2019mentioning
confidence: 99%